ENERGY CONSERVATION AS ONE OF THE COMPONENTS OF THE MANAGEMENT SYSTEM FOR THE SMART SUSTAINABLE WORKSPACES - Maksym Yakubovych; Vasyl Lyashkevych; Roman Shuvar (Електроніка та інформаційні технології)
Background. "Smart technologies" have grown rapidly thanks to advanced achievements in artificial intelligence (AI) and IoT. Big companies are interested in the concept of "smart rooms" or "smart workplaces" because these technologies allow them to reduce the costs of maintaining workplaces and focus on sustainable production without redundant waste.